Persepsi Konsumen Terhadap Keinginan Pembelian Produk Halal Di Kota Pekanbaru - Saru Reza; Mifta Hasda; Muhammad Syaipudin; Syafnur Muhammad Rizky (Global Sustainability Research Institute, 2024)
Introduction: This research aims to analyze consumer perceptions regarding their desire to purchase halal products in Pekanbaru City. In the era of globalization and increasing awareness of the importance of halal products, understanding the factors that influence consumer desires is very important. Methods: This research uses a quantitative approach with survey methods. The survey was conducted on 204 respondents who were randomly selected from various areas in Pekanbaru City. Data was collected using a questionnaire. Data analysis was carried out using descriptive analysis and analyzed simply based on the highest indicator value of the variable being observed. Results: This research shows that the majority of respondents in Pekanbaru City have good knowledge about the latest halal logo from BPJPH and BPJPH's authority in managing halal certification. Respondents also felt that halal labeling was very helpful in making product purchasing decisions, and they tended to choose products labeled halal even though the price was more expensive. Quality standards, quality, and halal guarantees are the main considerations in purchasing products. Conclusion and Suggestions: This research concludes that consumers in Pekanbaru City pay great attention to knowledge about halal logos and certification authorities in choosing halal products. The halal label is considered to guarantee product quality, and consumers are willing to pay more for products labeled halal. Producers and marketers are advised to increase information and education about halal products, maintain brand quality and reputation, and ensure products have clear and reliable halal certification.